A Study on College Students’ Entrepreneurship Practice in Guangzhou :A Case of GDUFS - WU, Yiming (Advances in Social Sciences Research Journal, 2015)
In the past 10 years, the ratio of college graduates’ self-employment has demonstrated a rising tendency in China. During the process of starting business, college students are inclined to get involved into various troubles as lacking of experience. This research aims to analyze the plights at different stages of starting business, and try to give some suggestions based on the case of Guangdong University of Foreign Studies(GDUFS).